Post Central Line Insertion Complication Rate in Tertiary Care Hospital Comparison between Different Sites - Mahmood, Muhammad Ahsan; Saleem, Salman; Nawaz, Sadaf; Ghawas, Ali; Amer, Ahsan; Amer, Ahmed (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the post-central line insertion complication rate at various central venous catheterization sites in a tertiary care teaching hospital.Study Design: Prospective comparative study.Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Aug 2022 to Jan 2023.Methodology: Data from 126 patients who had central venous line insertion was collected, and it was assessed for early and delayed complications related to central venous line insertion with respect to site.Results: The mean age of patients undergoing central venous line insertion was 55.74±12. A total of 38 mechanical complications over 54 years were documented in this study. The rate of pneumothoraxes with internal jugular insertion was 9(7.14%), although this was not statistically significant. Total arterial injuries were 21(0.16%), 10(0.07%) in internal jugular, and 11(0.08%) in femoral. The rate at which one or more delayed complications occurred following a given CVC placement was 8(6.4%). By body part, 31(24.6%) of interjugular central venous catheters and 38(30.12%) of femoral central venous catheters had at least one delayed problem. The total catheter-related blood stream infection was higher with central lines inserted in the femoral vein. No complications were reported in 37 patients.Conclusion: Both internal jugular and femoral sites cause more delayed complications than mechanical complications. At the femoral site, the catheter-related bloodstream infection rate was higher.